“City–ruin”. The image of the post-war Gdańsk in the photographs of Kazimierz Lelewicz - Polańska, Anna (City and War, 2021)
Metropolises and cities have always fascinated artists, including those who use photography. World War II brought a hitherto unknown image of the city–ruins. Those who survived the annihilation made an attempt to depict the destruction. The photographs were supposed to be a testimony of the cruelty of war, and years later they also became material used by researchers from many scientific disciplines. Here emerges the specificity of showing the ruins in the context of a photo, which can be a document, but also a piece of art. The ruins became a journalistic and artistic challenge for the creators. Images of the destroyed cities began to be exhibited in museums and galleries, not only in the first years after the end of World War II. In Poland, the way of showing the devastation of Warsaw is symptomatic compared to the cities in the Recovered Territories. The capital has become a symbol of the drama of the whole country. The image of the city from before 1939 was often compared with the image of war damage. The photographs of the ruined: Gdańsk, Szczecin and Wrocław, had a slightly different message. In these cities, they looked for evidence of Polish identity, a centuries-old tradition and historical belonging to the Polish state. The views of the destroyed cities were juxtaposed with the image of the country’s reconstruction, emphasizing the new geopolitical order. It is estimated that ninety percent of the historic center of Gdańsk was destroyed during World War II. In the fall of 1945, Kazimierz Lelewicz (1896–1986), an engineer and artist-photographer by education, came to such a ruined city. He began a long process of documenting the destruction and reconstruction of Gdańsk. What is striking in Lelewicz’s photographs is the juxtaposition of the image of a city–ruin, an extinct, autonomous space, with a city-building, full of life. This combination of images of the urban tissue has a very symbolic and allegorical meaning. In this context, the image of the ruin and the way it was interpreted by Kazimierz Lelewicz is also worth considering. The topic itself provokes the consideration of the theme of ruin in the discourse of memory or oblivion.